1992
DOI: 10.1001/jama.1992.03490230068030
|View full text |Cite
|
Sign up to set email alerts
|

Confidential HIV Testing and Condom Promotion in Africa

Abstract: A confidential HIV testing and counseling program was associated with increased use of condoms and reduced rates of gonorrhea and HIV in urban Rwandan women. The lack of risk reduction in HIV-negative women whose partner's serostatus was unknown was of concern. Interventions that promote HIV testing and counseling for both members of a couple should be considered in other high-prevalence areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(62 citation statements)
references
References 27 publications
4
58
0
Order By: Relevance
“…A noteworthy number of couples had discordant HIV status (18.0%) providing an important opportunity for prevention counseling. Other studies among discordant couples have found improved communication about sexual matters and increased condom use after couple counselling [1][2][3]21]. Moreover, prevention counseling has been associated with lower rates of HIV transmission in discordant couples [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A noteworthy number of couples had discordant HIV status (18.0%) providing an important opportunity for prevention counseling. Other studies among discordant couples have found improved communication about sexual matters and increased condom use after couple counselling [1][2][3]21]. Moreover, prevention counseling has been associated with lower rates of HIV transmission in discordant couples [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…VCT programs implemented outside of pMTCT have identified advantages in counseling couples rather than individuals. Couples counseling has been shown to be more successful in promoting behavior change [1], facilitating communication between couples [2] and decreasing HIV transmission [3]. In practice, it is often difficult to encourage individuals to participate in couples counselling [4][5][6][7]; however, some programs have improved participation rates through integrated approaches and community outreach [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A highly similar picture emerges from studies that examined STD acquisition rates between HIV-infected aware and unaware persons. [27][28][29][30] These studies were not included in the metaanalysis because of the qualitatively different nature of the outcome variable and the fact that the partner serostatus adjustment could not validly be applied to those studies. Of persons presenting at an STD clinic in New Orleans (1989-1991) with a first-time diagnosis of gonorrhea, new gonorrhea diagnoses were 50% lower during 2 to 3 years of follow-up in persons aware relative to unaware that they were HIV + .…”
Section: Discussionmentioning
confidence: 99%
“…From the results of these surveys researchers are able to calculate the percentage increase in condom use (Ford, Wirawan, Fajans, Meliawan, MacDonald & Thorpe, 1996;Fox, Bailey, Clarke-Martinez, Coello, Ordonez & Barahona, 1993;Ngugi et al, 1996;Visrutaratna et al, 1995;Williams et al, 1992); increase in knowledge about HIV transmission; behaviour change (Aplasca et al, 1995;Archibald, Chan, Wong, Goh & Goh, 1994;Asmoah-Adu, et al, 1994;Klepp et al, 1994;Munodawafa, Marty & Gwede, 1995;Schopper et al, 1995;Wilson et al, 1992;Wynendaele, Bomba, Manga, Bhart & Fransen, 1995;); and changes in perceptions of personal risk (Pauw, Ferrie, Villegas, Martínez, Gorter & Egger, 1996). Quantitative methodology is also used through pre-and post-intervention STD tests with project success being measured by significant declines in STD prevalence or incidence (Allen et al, 1992;Archibald et al, 1994;Bhave et al, 1995;Chipfakacha, 1993;Laga et al, 1994;Nymauryekung'e et al, 1997). Evaluation through the comparison of pre-and post-intervention HIV incidence or prevalence is also employed (Allen et al, 1992;Grosskurth et al, 1995;Nymauryekung'e et al, 1997).…”
Section: ) Over-reliance On Quantitative Methodologiesmentioning
confidence: 99%
“…Quantitative methodology is also used through pre-and post-intervention STD tests with project success being measured by significant declines in STD prevalence or incidence (Allen et al, 1992;Archibald et al, 1994;Bhave et al, 1995;Chipfakacha, 1993;Laga et al, 1994;Nymauryekung'e et al, 1997). Evaluation through the comparison of pre-and post-intervention HIV incidence or prevalence is also employed (Allen et al, 1992;Grosskurth et al, 1995;Nymauryekung'e et al, 1997). Modeling and estimations allow researchers to estimate the number of potential HIV infections interventions have prevented (Moses et al, 1991;Ngugi et al, 1996).…”
Section: ) Over-reliance On Quantitative Methodologiesmentioning
confidence: 99%